مساهمة السياسات الاقتصادية العمومية في ترقية قطاع التشغيل والقضاء على مشكلة البطالة في الجزائر - بن سمينة، عزيزة Bin Saminah, Azizah; طبنى، مريم Tebni, Mariam (جامعة العربي بن مهيدي أم البواقي - مخبر المالية، المحاسبة، الجباية والتأمين, 2016)
We will try through this briefing paper to the problem of unemployment, which is one of the dilemmas faced by most of the world at the present time, it is an economic problem, psychological, social, and political. And Algeria are among the countries that have suffered and still the problem of unemployment due to the economic crisis experienced during the nineties in addition to security conditions, these conditions have allowed unemployment to spill deep in the Algerian society, and thus influenced eloquent impact on economic policies, it worked to contain it by relying on individual initiatives to idle, and embodied in the form of small and medium projects, where experience has shown the effectiveness of this approach, however, it requires the need to embrace the state for him.
سنحاول من خلال هذه الورقة الإحاطة بمشكلة البطالة، والتي تعد إحدى المعضلات التي تواجه معظم دول العالم في الوقت الراهن، فهي مشكلة اقتصادية، نفسية، اجتماعية، وسياسية. والجزائر من بين الدول التي عانت ولا تزال من مشكلة البطالة بسبب الأزمة الاقتصادية التي عاشتها خلال التسعينات إضافة إلى الظروف الأمنية، هذه الظروف سمحت للبطالة بالامتداد في عمق المجتمع الجزائري، وبذلك أثرت تأثير بليغا في سياساتها. الاقتصادية، فعملت على احتواءها من خلال الاعتماد على المبادرات الفردية للبطالين، وتجسيدها في شكل مشاريع صغيرة ومتوسطة، حيث أثبتت التجارب فعالية هذا التوجه، غير أنه يقتضي ضرورة احتضان الدولة له.
Keywords: البطالة; الجزائر; السياسات الاقتصادية; العمل والعمال